Effect of bupivacaine concentration and formulation on canine chondrocyte viability in vitro. Issue 3 (13th February 2021) - Rengert, Roger; Snider, Darren; Gilbert, Peter J.
Abstract: Objective: To quantitate bupivacaine concentration and formulation effects on chondrocyte viability in vitro. Study design: Controlled laboratory study. Sample population: Primary canine chondrocyte isolates. Methods: Cell passage 3 and 4 canine chondrocytes were exposed to 0.9% saline; canine chondrocyte growth medium; 0.4, 0.5, 0.6, 1.5, 2.5, 3.5, or 5 mg/mL preservative‐free standard formulation bupivacaine (SFB); or 13.3 or 6.65 mg/mL liposomal encapsulated bupivacaine (LEB) for 1 hour. Chondrocyte viability and clonogenicity were quantitated with 3‐(4, 5‐dimethylthiazol‐2‐31 yl)‐2, 5‐diphenyltetrazolium bromide (MTT) and clonogenic assays, respectively. Differences among concentrations and formulations were assessed with Kruskal‐Wallis and Dwass‐Steel‐Critchlow‐Fligner post hoc tests. Results: Growth medium had the highest cell viability based on MTT metabolism. Similarly, all LEB concentration groups had higher cell viability compared with SFB concentration cells treated with 3.5 or 5 mg/mL SFB ( P  < .03). Among SFB concentrations, cell viability was higher at 0.6 mg/mL compared with at 2.5 mg/mL or greater ( P  < .03). Cell clonogenicity was not significantly different between saline, culture medium, or 0.5 mg/mL SFB. Clonogenicity was lower with all tested LEB concentrations compared with saline or medium ( P  < .02). Conclusion: In vitro toxicity of SFB on canine chondrocytes is concentration dependent. Liposomal encapsulated bupivacaine may have time‐dependent effects resulting in chondrotoxicity. Clinical significance: Clinically relevant concentrations of SFB after a single injection may not result in chondrotoxic effects in vitro. Liposomal encapsulated bupivacaine should not be used in the articular environment.